An Impact of Financial Literacy and Behavioural Biases on Share Market Investment Awareness - D, Paranichandran; Ilankadhir, Dr. M (International Journal of Accounting and Economics Studies, 2025)
This study investigates the factors influencing investment awareness among individuals, with a specific focus on financial literacy, personal interest, social media influence, and environmental factors. In an era where financial markets are increasingly accessible, under-‎standing what drives individuals to become aware and active investors is crucial. A structured online survey using a Google Form was ‎conducted to collect primary data from 153 respondents. The questionnaire included closed-ended questions designed to measure ‎investment awareness and its associated factors. Statistical analyses, including correlation and multiple regression, were applied to examine the relationships between variables. The findings reveal that financial literacy (r = 0.602), personal interest (r = 0.534), social media ‎influence (r = 0.491), and environmental factors (r = 0.504) all show significant positive correlations with investment awareness. ‎Regression results further indicate that financial literacy and environmental factors have a substantial impact on individuals’ investment ‎decisions. Hypothesis testing confirmed that all four independent variables significantly influence investment awareness, with varying ‎levels of impact. This study underscores the importance of targeted financial education, personalised engagement strategies, and leveraging digital platforms to enhance awareness and participation in financial markets. The insights derived can inform policymakers, educators, and financial institutions in designing effective programs to boost investment participation‎.
Keywords: Share Market; Investment Awareness; Financial Literacy; Social Media Influence; Environment